METHODS OF INCREASING WHEAT PRODUCTION IN MEXICO - RUPERT, J; BORLAUG, NE (Hospital General, CD MEXICO, DF, MEX, 1900)
Although cancer-stimulating, diethyl-ethylbestrol dipropionate did not produce recognizable symptoms in exptl cattle, but it produced a marked increase in milk production
PHYS REV B
Keywords: METHODS, WHEAT PRODUCTION, MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL